TTIP and intra-European trade: boon or bane? - Rahel Aichele; Gabriel Felbermayr; Inga Heiland (ifo Institute - Leibniz Institute for Economic Research at the University of Munich, 2016)
The European Union is the world's largest and deepest free trade zone. Amongst its members, ithas abolished tariffs and lowered non-tariff barriers. This has led to trade creation within Europeand to trade diversion between EU countries and outsiders. The Transatlantic Trade and Investment Partnership TTIP (or other trade agreements with third countries) will undo some of theseeffects by means of preference erosion, so that cross-country trade links within Europe may loserelative prominence at the expense of additional trade with the US. However, the presence of arich fabric of regional value chains in Europe and substantial income effects could counter thisdevelopment. In this paper, we provide insights based on a New Quantitative Trade Model. Weshow that TTIP could indeed lower trade integration in Europe since predicted income effectsturn out not to be large enough to overcome the effects of preference erosion. Moreover, tradediversion effects in value added terms tend to be even more pronounced than in gross (official)trade flows. However, there is substantial heterogeneity across sectors and countries. To avoidthe political costs associated with weaker intra-EU ties, Europe should deepen the single marketalongside the formation of large trade agreements with outsiders.
Keywords: F13; F14; F17; 330; TTIP; single market; European integration